Assessing Confidentiality in the Lawyer-Client Relationship: A Client Perspective - Hunter, Richard J.; Shannon, John H. (Advances in Social Sciences Research Journal, 2022)
This article will provide information on issues relating to the attorney-client relationship and the attorney-client privilege, the duty of confidentiality, the crime- fraud exception, the work product doctrine, and other exceptions to the general duty of confidentiality existing in the lawyer-client relationship. The article is based on an analysis of decisional cases and selected commentaries found in law reviews and writings of prominent legal practioners.